Efficacy of copeptin in distinguishing COVID‐19 pneumonia from community‐acquired pneumonia. Issue 5 (17th February 2021) - Kuluöztürk, Mutlu; İn, Erdal; Telo, Selda; Karabulut, Ercan; Geçkil, Ayşegül Altıntop
Abstract: The clinical symptoms of community‐acquired pneumonia (CAP) and coronavirus disease 2019 (COVID‐19)‐associated pneumonia are similar. Effective predictive markers are needed to differentiate COVID‐19 pneumonia from CAP in the current pandemic conditions. Copeptin, a 39‐aminoacid glycopeptide, is a C‐terminal part of the precursor pre‐provasopressin (pre‐proAVP). The activation of the AVP system stimulates copeptin secretion in equimolar amounts with AVP. This study aims to determine serum copeptin levels in patients with CAP and COVID‐19 pneumonia and to analyze the power of copeptin in predicting COVID‐19 pneumonia. The study consists of 98 patients with COVID‐19 and 44 patients with CAP. The basic demographic and clinical data of all patients were recorded, and blood samples were collected. The receiver operating characteristic (ROC) curve was generated and the area under the ROC curve (AUC) was measured to evaluate the discriminative ability. Serum copeptin levels were significantly higher in COVID‐19 patients compared to CAP patients (10.2 ± 4.4 ng/ml and 7.1 ± 3.1 ng/ml; p  < .001). Serum copeptin levels were positively correlated with leukocyte, neutrophil, and platelet count ( r  = −.21, p  = .012; r  = −.21, p  = .013; r  = −.20, p  = .018; respectively). The multivariable logistic regression analysis revealed that increased copeptin (odds ratio [OR] = 1.183, 95% confidence interval [CI], 1.033–1.354; p  = .015) and CK‐MB (OR = 1.052, 95% CI, 1.013–1.092; p  = .008) levels and decreased leukocyte count (OR = 0.829, 95% CI, 0.730–0.940; p  = .004) were independent predictors of COVID‐19 pneumonia. A cut‐off value of 6.83 ng/ml for copeptin predicted COVID‐19 with a sensitivity of 78% and a specificity of 73% (AUC: 0.764% 95 Cl: 0.671–0.856, p  < .001). Copeptin could be a promising and useful biomarker to be used to distinguish COVID‐19 patients from CAP patients.